Plantar pressures in three types of indigenous footwear, commercial minimal shoes, and conventional Western shoes, compared to barefoot walking. (2nd January 2021) - Willems, Catherine; Curtis, Rory; Pataky, Todd; D'Août, Kristiaan
Abstract: Humans evolved as barefoot walkers, and only started to use footwear recently in evolutionary history. It can be questioned what the effect is of footwear on gait. This effect has previously been studied for a range of conventional and athletic footwear, but this study focuses on indigenous footwear which does not have the features commonly associated with conventional footwear, such as a raised heel, a relatively narrow toe box, arch support, and a firm heel cup. We will assess whether such footwear can be considered functionally 'minimal' and simulate barefoot walking, by analysing spatial and temporal aspects of plantar pressure distribution. We first compare the 2 D spatial distribution of plantar pressure, using 2 D Statistical Parametric Mapping, between four populations walking barefoot and with indigenous or commercial minimal shoes. We compared Indians wearing sandal-like footwear ('Kolhapuri'), Scandinavians wearing boot-type footwear ('Nuvttohat'), Namibian San wearing sandal-like footwear ('N!ang n|osi') and Western Europeans wearing a commercial minimal shoe, and conventional Western footwear. Within each population, indigenous and commercial barefoot footwear data were compared to barefoot walking. No statistically significant differences were found within-population between all footwear conditions and barefoot walking. Second, we question whether there were 1 D temporal differences in centre of pressure movements between three footwear conditions (barefoot, commercial minimal, conventional Western) within one, Western, population. Using 1 D Statistical Parametric Mapping, differences between these three conditions are shown, with barefoot walking keeping a more proximal CoP position than both footwear conditions during most of push-off phase. Based on plantar pressure recordings, we conclude that all indigenous and commercial minimal shoes can functionally be considered 'minimal footwear', but with some differences to barefoot walking.